The morphodynamics of sediment movement through a reservoir during dam removal - Bromley, Chris (2008)
Dam removal has recently emerged as a growing trend in river rehabilitation in the United States. The rate of dam removal has been increasing rapidly since 2000, but is doing so with large gaps in our understanding of how the fluvial system will respond to this disturbance. Most of the structures removed to date have been relatively small and, in the vast majority of cases, have not received any pre- or post-removal monitoring. Very few large structures have been removed but, when such removals occur or are proposed, they tend to attract more monitoring activity because of the generally larger volumes of water and sediment involved. It is thus important to understand the form-process-response interactions that occur during the removal of large dams and the extent to which these may be applicable to other removals of varying sizes.